Hemorrhoidectomy for elderly patients aged 75 years or more, before and after studies. (July 2020) - Yamamoto, Masateru; Ikeda, Masanobu; Matsumoto, Tomio; Takemoto, Masahiko; Sumimoto, Ryo; Kobayashi, Tsuyoshi; Ohdan, Hideki
Abstract: Background: The incidence of hemorrhoids requiring hemorrhoidectomy among the elderly has been increasing. Old age is sometimes considered a contraindication for surgery. The relationship between age and complications of hemorrhoidectomy for elderly patients is not well established. This study aimed to compare the clinicopathological features and postoperative outcomes of hemorrhoidectomy in the elderly (≥75 years old) and non-elderly patients (<75 years old). Methods: A total of 100 patients who underwent hemorrhoidectomy for hemorrhoids of Goligher classification grades 3 and 4 at our institution between 2014 and 2018 were enrolled. The clinical characteristics were compared between the elderly and non-elderly patients. Pain scores were measured at 6, 12, 24, and 48 h after surgery. The risk factors for postoperative complications were identified. Results: A total of 34 patients were classified as elderly patients. In the elderly group, aspartate aminotransferase levels were higher while the albumin levels and cholinesterase levels were lower and the platelet counts were significantly lower. The blood urea nitrogen levels were higher and estimated glomerular filtration rates and hemoglobin levels were significantly lower in the elderly group. The pain scores significantly decreased at 48 h postoperatively compared to those recorded at 6 h postoperatively in both groups. Multivariate analysis identified Goligher classification grade 4 and high neutrophil to lymphocyte ratio at the indicators of complications. Conclusions: Hemorrhoids due to impairment of liver function and kidney function were dominant in elderly patients. Aging itself was not a risk factor for postoperative complications. Highlights: The feasibility of hemorrhoidectomy for the elderly is not remained clear. The incidence of postoperative complications was comparable regardless of age. The risk factor for complication was Goligher classification grade 4 and high NLR.